Modernisation, nationalisation, désislamisation - Johann Strauss (Revue des Mondes Musulmans et de la Méditerranée)
Studies concerned with linguistic Reform (or Revolution) of Turkish have tended to neglect the role played by religion in the context of the modernization of the Turkish language in the 19th-20th centuries. The debate started very early with various arguments. Religious arguments revolve around the issue of the script and the creation of a modern terminology. The attachment to the ‘Muslim script’ and to the lexical resources provided by the Arabic derivational system (particularly regarding technical terms) was extremely strong. The desire to create a scientific vocabulary on a par with the other ‘Islamic languages’ guided a nationalist thinker like Ziya Gökalp. It is only during the 1930s that under the influence of a new republican nationalism, a trend began toward what can be defined as a ‘de-Islamization’. In the language domain, the evolution, which started with the adoption of the Latin script and went on with the elimination of Arabic and Persian elements has become irreversible today, even if some Islamists reject such changes. As for the language of religion, the innovative trend seems to have reached its limits, although the turkicization of the language of prayers continues to be discussed.